Rapid induction by wounding and bacterial infection of an S gene family receptor-like kinase gene in Brassica oleracea. - Pastuglia, M (1997)
A receptor-like kinase, SRK, has been implicated in the autoincompatible response that leads to the rejection of self-pollen in Brassica plants. SRK is encoded by one member of a multigene family, which includes several receptor-like kinase genes with patterns of expression very different from that of SRK but of unknown function. Here, we report the characterization of a novel member of the Brassica S gene family, SFR2. RNA gel blot analysis demonstrated that SFR2 mRNA accumulated rapidly in response both to wounding and to infiltration with either of two bacteria: Xanthomonas campestris, a pathogen, and Escherichia coli, a saprophyte. SFR2 mRNA also accumulated rapidly after treatment with salicylic acid, a molecule that has been implicated in plant defense response signaling pathways. A SFR2 promoter and reporter gene fusion was introduced into tobacco and was shown to be induced by bacteria of another genus, Ralstonia (Pseudomonas) solanacearum. The accumulation of SFR2 mRNA in response to wounding and pathogen invasion is typical of a gene involved in the defense responses of the plant. The rapidity of SFR2 mRNA accumulation is consistent with SFR2 playing a role in the signal transduction pathway that leads to induction of plant defense proteins, such as pathogenesis-related proteins or enzymes of phenylpropanoid metabolism.